MENINGKATKAN KEMAMPUAN KEPALA SEKOLAH DALAM MELAKUKAN SUPERVISI AKADEMIK MELALUI MODEL PENDAMPINGAN DI SMP NEGERI 2 WAIGETE - alfares, Thomas (Aksara Public, 2018)
The mentoring model that supervisors are doing together with the Headmaster in academic supervision is done continuously in educational interaction, positive communication in accordance with the needs of the principal. The accompaniment of this research used the design of PTK cycle model by Kemmis & Taggart. At each cycle there are four components of the activities of the plan, action, monitoring, reflection and evaluation. The results of the evaluation in cycle I was the implementation of supervision by the head of the school into the category has not been good, or a new average of 55% indicator that is met. The results of evaluation in cycle II, indicate that the principal who supervise academic with the method of accompaniment has increased in good category, or an average of 88% indicator is met. The results of school action research indicate that the mentoring model can improve the principal's skill in performing academic supervision.